Molecular Mechanisms of Colistin Resistance in Klebsiella pneumoniae Causing Bacteremia from India—A First Report - Pragasam, Agila K.; Shankar, Chaitra; Veeraraghavan, Balaji; Biswas, Indranil; Nabarro, Laura E. B.; Inbanathan, Francis Y.; George, Biju; Verghese, Santhosh (Frontiers in Microbiology, 2017)
Background: Colistin has long been the drug of last resort in the treatment of carbapenem resistant Klebsiella pneumoniae. Carbapenem resistance in K.pneumoniae is increasing and is as high as 44% in India. The rise in rates of carbapenem resistance has resulted in increased use of colistin which has led to the emergence of colistin resistance. Colistin resistance is mainly mediated by alteration in the lipopolysaccharide (LPS) of the bacterial outer membrane with the addition of L-Ara4-N and PEtN molecules. These alterations are mediated by mutations in several genes involved in lipidA modifications, most commonly mutations in mgrB gene. The recent emergence of plasmid mediated resistance due to mcr-1 and mcr-2 genes poses a global risk. This study characterizes eight colistin resistant K.pneumoniae isolates from bacteremic patients at Christian Medical College, Vellore, India, using whole genome sequencing. Material/methods: Eight K. pneumoniae were isolated from blood culture during 2013 and 2015 at the Department of Clinical Microbiology, Christian Medical College, India. Antimicrobial susceptibility testing was performed and minimum inhibitory concentration (MIC) was determined for colistin and polymyxin B by broth-micro dilution method. Whole genome sequencing was performed using Ion Torrent and the genome of all eight isolates was analyzed. Results: The eight isolates were resistant to all antimicrobials except tigecycline. The MIC of colistin and polymyxin B ranged from 4 to 1024 µg/ml and 0.5 to 2048 µg/ml respectively. Multiple mutations were observed in chromosomal genes involved in lipid A modifications. mcr-1 and mcr-2 gene was absent in all isolates. The most significant mutations were in mgrB gene. Among the eight isolates, four isolates belonged to sequence type ST231, three to ST14 and one to ST147. Seven isolates had the blaOXA-48 like gene, whilst one co-expressed blaNDM-1 and blaOXA-48 like genes resulting in carbapenem resistance. Conclusions: Mutations in the mgrB gene are responsible for resistance to colistin in this study. Multiple mutations have been observed including silent mutations, point mutations, insertions and/or deletions. Colistin resistance is an increasing concern in carbapenem resistant K.pneumoniae and the drug should be used judiciously.